Générations et rapports de générations - Mauger, Gérard (Daimon Revista Internacional de Filosofia, 2009)
This article aims at clarifying the notion of generation by resorting to the everyday life distinction between social and family generations. First, it highlights two useful analytical perspectives to shed light on the way distinct social generations are generated: the transformation of socialising frameworks (i. e. of «modes of reproduction») on the one hand; the existence of «life course events» on the other. Secondly, it distinguishes between three types of inheritance in the relationships between family generations: material inheritance, cultural inheritance, and what I have labelled «the poor inheritance» – both the inheritance of the poor and the specific «poor» resources it involves.